Enhanced luminescence and tunable magnetic properties of lanthanide coordination polymers based on fluorine substitution and phenanthroline ligand. Issue 29 (24th May 2019) - Feng, Xun; Shang, Yapei; Zhang, Heng; Li, Rongfang; Wang, Weizhou; Zhang, Daoming; Wang, Liya; Li, Zhongjun
Abstract : Lanthanide coordination polymers with F-substituted carboxylate tectonics and phenanthroline ligands exhibit emission from the visible to near-infrared region with long lifetime. Dy(iii ) compounds show temperature dependent and field induced single molecule magnetism. Abstract : A family of highly stable lanthanide coordination polymers incorporating fluorine-substituted carboxylate tectonics and the rigid ligand phenanthroline, namely, {[Ln m (Tfbda) n (Phen)2 ·2H2 O]·2H2 O} z, (Ln = Pr (1 ), Ho (4 ) and Gd (7 ), m = 2, n = 3); {[Ln3 (Tfbda) m 1 (Tfba) m 2 (Phen) n ·2H2 O]·H2 O} z ( z > 1, Ln = Dy (3 ), Er (5 ) and Yb (6 ), m 1 = 4, m 2 = 1, n = 3); [Ln2 (H2 Tfbda)4 (Phen)2 ·(H2 O)2 ]·Phen (Ln = Nd (2 )), Tfbda = 3, 4, 5, 6-tetrafluoro-benzene-1, 2-dioic acid, Tfba = 2, 3, 4, 5-tetrafluorobenzoic acid have been afforded under hydrothermal conditions. The series of coordination polymers exhibited diverse structural motifs, from dinuclear cluster to 1-D chain arrary, displaying efficiently sensitized luminescence over a spectral range from visible to near-infrared (NIR) region and a long lifetime, due to efficient energy transfer from fluorine-substituted ligands to Ln(iii ) centers in solid state. Slow relaxation magnetization and significant frequency- and temperature-dependent peaks were observed in trinuclear Dy(iii )-based coordination polymer3 . DC magnetic susceptibility studies reveal the existence of weak ferromagnetic interaction within7 .